Reading Comprehension Achievement on Narrative Text by Using REAP Strategy - Fitri Amalia; Rita Inderawati; Erlina Erlina (Pendidikan Bahasa Inggris STKIP Nurul Huda, 2018)
This study was conducted to find out whether or not: (1) there was a significant difference in narrative reading comprehension achievement of the eighth grade students of SMP Muhammadiyah 1 Palembang before and after they were taught by using REAP strategy, (2) there was a significant difference in reading comprehension achievement on narrative text between the eighth grade students of SMP Muhammadiyah 1 Palembang who were taught by using REAP strategy and those who were not. The population of the study was the eighth-grade students of SMP Muhammadiyah 1 Palembang in the academic year 2015/2016 consisting of 240 students. The sample was 70 students who were divided into experimental and control group that were taken by using purposive sampling technique. To collect the data and to measure students' reading comprehension achievement, the reading comprehension test was given.The test was administered twice as a pretest and posttest. The result from paired sample t-test showed that t-obtained was higher than t-table (11.604>2.0301) at the significance level of p<0.05. It means that H01 was rejected and there was a significant difference in students’ reading comprehension achievement of experimental group. The result from independent sample t-test of the post-test in both experimental and control groups showed that there was a significant difference at the significance level of p<0.05 and t-obtained was higher than t-table (2.029>1.9955). Therefore, there was a significant difference in reading comprehension achievement between the students who were taught by using REAP strategy and those who were not.